2015
DOI: 10.1016/j.jcis.2015.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking to enhance colloidal stability and redispersity of layered double hydroxide nanoparticles

Abstract: This article introduces a strategy for stabilizing and redispersing layered double hydroxide (LDH) nanoparticles by crosslinking bovine serum albumin (BSA) coated onto the surface. The strategy involves optimization of the amount of the crosslinking agent glutaraldehyde (GTA) to achieve minimal aggregation and ready redispersion. LDH nanoparticles were prepared by co-precipitation and hydrothermal treatment, with subsequent BSA coating at the BSA/LDH mass ratio of 5:2. BSA coated onto LDH nanoparticles was cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
4
45
0
Order By: Relevance
“…LDH clay nanoparticles were synthesised and prepared under sterile conditions as previously described [48]. In brief, 10 mL 700 mM MgCl 2 and 300 mM…”
Section: Preparation and Characterisation Of Clay Nanoparticlesmentioning
confidence: 99%
“…LDH clay nanoparticles were synthesised and prepared under sterile conditions as previously described [48]. In brief, 10 mL 700 mM MgCl 2 and 300 mM…”
Section: Preparation and Characterisation Of Clay Nanoparticlesmentioning
confidence: 99%
“…Interestingly, the natural biomolecules such as serum albumin have been demonstrated as a promising agent against LDH particle aggregation via surface coating. Our team has recently developed a bovine serum albumin (BSA) precoating strategy to effectively prevent particle aggregation in biological solutions including saline, PBS, and serum (Figure c) . Our results have revealed that LDH nanoparticles with the size of 110 nm are able to disperse well at an appropriate BSA/LDH mass ratio (5:2) with the rationally designed mixing method .…”
Section: Improved Stability By Surface Engineeringmentioning
confidence: 99%
“…For instance, the therapeutic agents are often in the format of dry powder that needs dispersion in an electrolyte solution such as 0.9% saline or 5% glucose before administration . However, the LDH nanoparticles quickly form serious aggregates by Bernal stacking during the drying process, and nanoparticles, particularly once dried, cannot be redispersed in the electrolyte media …”
Section: Improved Stability By Surface Engineeringmentioning
confidence: 99%
“…[21][22][23][24] Among the choices, layered double hydroxide (LDH) nanomaterials have been very attractive due to their superior merits including good biocompatibility, biodegradability like biomolecule based nano-carriers, [25][26][27][28] and pH sensitive drug release characteristics. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Despite these advantages, there are also issues when LDH nanoparticles are employed in delivering PS molecules for photodynamic therapy. In particular, owing to the lack of functional groups on the surface, these nanomaterials are not stable in blood circulation.…”
mentioning
confidence: 99%